ANALISIS CONTENT MARKETING DAN ELECTRONIC WORD OF MOUTH (E-WOM ) TERHADAP KEPUTUSAN PEMBELIAN GENERASI Z PADA MEDIA SOSIAL TIK-TOK (STUDI KASUS GENERASI Z KABUPATEN DHARMASRAYA) - Mayroza Wiska; Fenisi Resty; Hidayatul Fitriani Hidayatul Fitriani (Universitas Sarjanawiyata Tamansiswa, 2022)
The rapid development of technology makes social media one of the most effective marketing strategies to influence purchasing decisions. Moreover, during the current COVID-19 pandemic, various policies have been implemented to minimize the spread of the virus, which has led many companies to start looking at tik-tok as a platform for marketing their products. Because tik-tok is a social media platform that has just emerged and is very popular during the pandemic, it occupies the fourth position as the most widely used social media platform, where most of its users are from Generation Z. Seeing this phenomenon, this research was conducted to find out and analyze what kind of impact is caused by content marketing and electronic word of mouth (e-WOM) on the purchasing decisions of Generation Z on tik-tok social media in Dharmasraya Regency. The purpose of this study was to determine and analyze